Comparing Asynchronous and Synchronous Video versus Text Based Discussions in an Online Teacher Education Course - Cynthia Clark (Online Learning, 2015)
The purpose of this study was to investigate whether asynchronous video posts and synchronous videoconferencing would create higher levels of teaching and social presence within an online course when compared with the university’s current text-based discussion platform. Undergraduate students in an online teacher education course were randomly assigned to either the text-based discussion platform or the video-based discussion platform. A switched replications design was used and halfway through the semester students switched platforms. Analysis of student interviews and surveys administered at the end of the semester indicated self-reported perceptions of social and teaching presence were significantly higher when using the video-enabled discussion site. Implications of the added value of video, both in synchronous and asynchronous contexts, are discussed and recommendations for further study are provided.